2019
DOI: 10.1186/s12960-019-0392-2
|View full text |Cite|
|
Sign up to set email alerts
|

Are the Global Strategic Directions for Strengthening Nursing and Midwifery 2016–2020 being implemented in countries? Findings from a cross-sectional analysis

Abstract: Background Nurses and midwives are the largest component of the health workforce in many countries. The World Health Organization (WHO) together with its partners facilitates the joint development of strategic policy guidance for countries to support the optimization of their nursing and midwifery workforce. The Global Strategic Directions for Strengthening Nursing and Midwifery 2016–2020 (SDNM) is a global policy guidance tool that provides a framework for Member States, the WHO and its partners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…midwives collecting or sharing data) [ 43 , 65 , 90 ] • Midwives were unable to practice to full scope because of inconsistent standards of education and professional regulation [ 78 , 91 , 106 ] • Globally, there was a general lack of knowledge regarding the International Confederation of Midwives’ Global Standards for Midwifery Education, which was a barrier to the provision of quality midwifery education [ 53 , 66 , 87 , 107 , 108 ] • Midwives were not practicing to their legislated full scope of practice (Canada), barriers included (1) hospitals — scope restrictions; (2) capping of the number of midwives granted hospital privileges; (3) capping the number of births attended by midwives; and (4) inconsistent midwifery policies across hospitals [ 52 , 77 ] • Healthcare reforms increased the centralisation of decision-making, which created barriers to change (Australia) [ 95 ] • Combination of regulatory processes and health systems that promoted birth as a natural process; favoured professional midwifery care (Nordic countries) [ 8 , 62 , 86 , 91 , 99 ] • Accreditation mechanisms supported midwifery education programmes and institutional capacities [ 63 , 70 , 93 , 107 ] • Environments that allowed midwives to practice autonomously and to full scope of practice [ 74 ] • Expanded scope from providing skilled delivery care to include SRHR ranging from abortion, family planning, screening (diabetes and several forms of cancer), immunisations, palliative care, and public health and promotion [ 10 13 , 55 , 74 , 94 , 109 113 ] • Increased contraceptive prevalence rate (Nigeria) by engaging midwives in provision of family planning services [ 114 ] • Engagement of midwives within broader humanitarian emergency contexts (e.g. conflict, epidemics, and natural disasters) [ 46 ] •...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…midwives collecting or sharing data) [ 43 , 65 , 90 ] • Midwives were unable to practice to full scope because of inconsistent standards of education and professional regulation [ 78 , 91 , 106 ] • Globally, there was a general lack of knowledge regarding the International Confederation of Midwives’ Global Standards for Midwifery Education, which was a barrier to the provision of quality midwifery education [ 53 , 66 , 87 , 107 , 108 ] • Midwives were not practicing to their legislated full scope of practice (Canada), barriers included (1) hospitals — scope restrictions; (2) capping of the number of midwives granted hospital privileges; (3) capping the number of births attended by midwives; and (4) inconsistent midwifery policies across hospitals [ 52 , 77 ] • Healthcare reforms increased the centralisation of decision-making, which created barriers to change (Australia) [ 95 ] • Combination of regulatory processes and health systems that promoted birth as a natural process; favoured professional midwifery care (Nordic countries) [ 8 , 62 , 86 , 91 , 99 ] • Accreditation mechanisms supported midwifery education programmes and institutional capacities [ 63 , 70 , 93 , 107 ] • Environments that allowed midwives to practice autonomously and to full scope of practice [ 74 ] • Expanded scope from providing skilled delivery care to include SRHR ranging from abortion, family planning, screening (diabetes and several forms of cancer), immunisations, palliative care, and public health and promotion [ 10 13 , 55 , 74 , 94 , 109 113 ] • Increased contraceptive prevalence rate (Nigeria) by engaging midwives in provision of family planning services [ 114 ] • Engagement of midwives within broader humanitarian emergency contexts (e.g. conflict, epidemics, and natural disasters) [ 46 ] •...…”
Section: Resultsmentioning
confidence: 99%
“…• Strong leadership from midwifery professional associations engaged in policy dialogue and decision-making to advance universal health coverage and meeting health-related UN Sustainable Development Goals [ 8 , 63 , 66 , 71 , 90 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following publication of the original article [ 1 ], the authors identified an error in Table 2 . The correct table is given below.…”
mentioning
confidence: 99%